2017
DOI: 10.1186/s13059-017-1159-5
|View full text |Cite
|
Sign up to set email alerts
|

RNF40 regulates gene expression in an epigenetic context-dependent manner

Abstract: BackgroundMonoubiquitination of H2B (H2Bub1) is a largely enigmatic histone modification that has been linked to transcriptional elongation. Because of this association, it has been commonly assumed that H2Bub1 is an exclusively positively acting histone modification and that increased H2Bub1 occupancy correlates with increased gene expression. In contrast, depletion of the H2B ubiquitin ligases RNF20 or RNF40 alters the expression of only a subset of genes.ResultsUsing conditional Rnf40 knockout mouse embryo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(98 citation statements)
references
References 71 publications
17
79
0
Order By: Relevance
“…39 Whether these functions are used in meiosis or not still need further investigation. On the other hand, histone is not the only substrate of RNF20.…”
mentioning
confidence: 99%
“…39 Whether these functions are used in meiosis or not still need further investigation. On the other hand, histone is not the only substrate of RNF20.…”
mentioning
confidence: 99%
“…Past studies have reported an extension of H3K4me3 into the transcribed region of genes displaying a particularly high transcriptional elongation rate (31), as well as a close link between H2Bub1 and transcriptional elongation (23). Consistently, we recently demonstrated that loss of RNF40-mediated H2B monoubiquitination results in the narrowing of H3K4me3 domains near the transcriptional start site (TSS) of important cell fate-determining genes displaying high elongation rates (22).…”
Section: Introductionmentioning
confidence: 60%
“…We generated a tri-transgenic MMTV- Erbb2 ; MMTV-Cre; Rnf40 f lox mouse line with mammary tissue-specific co-expression of HER2 and Cre-recombinase, and a floxed Rnf40 allele. This approach enabled us to achieve a simultaneous HER2 overexpression and mammary epithelium-specific ablation of Rnf40 (18,22). Consistent with our findings in human HER2-positive BC lesions, MMTV- Erbb2; Rnf40 wt/wt tumors did not display a loss of either RNF40 or H2Bub1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations